2017
DOI: 10.4103/jnrp.jnrp_381_17
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Road Traffic Injury to Pediatric Traumatic Brain Injury in Southern Thailand

Abstract: Background:Motor vehicle is a major transportation in Southern Thailand as the result of road traffic injury and death. Consequently, severe disability and mortality in pediatric traumatic brain injury (TBI) were observed from traffic accident, particularly motorcycle accident. To identify the risk of intracranial injury in children, the association of treatment outcome with various factors including mechanisms of injury, clinical characteristics, and intracranial pathology can be assessed.Materials and Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 20 publications
2
19
0
5
Order By: Relevance
“…The most common cause of traffic injury in Thailand is motorcycle crashes. 12 24 Our study also found that motorcycle crashes were the leading cause of injury (62.2%), and a history of alcohol use may be responsible for these injuries; as 78.9% of these patients declared that they had been drinking alcohol before involvement in a motorcycle accident. Alcohol consumption may increase seizure threshold by acting on gamma-aminobutyric acid receptors, while cessation of drinking may lower seizure threshold with upregulation of N-methyl-D-aspartate receptor.…”
Section: Discussionsupporting
confidence: 55%
“…The most common cause of traffic injury in Thailand is motorcycle crashes. 12 24 Our study also found that motorcycle crashes were the leading cause of injury (62.2%), and a history of alcohol use may be responsible for these injuries; as 78.9% of these patients declared that they had been drinking alcohol before involvement in a motorcycle accident. Alcohol consumption may increase seizure threshold by acting on gamma-aminobutyric acid receptors, while cessation of drinking may lower seizure threshold with upregulation of N-methyl-D-aspartate receptor.…”
Section: Discussionsupporting
confidence: 55%
“…10 Finally, the GOS scores were dichotomized into favorable (GOS scores 4 and 5) and unfavorable (GOS scores 1-3) categories. 2,28 The study was performed with the approval of the Ethics Committee of the Faculty of Medicine, Songklanagarind Hospital, Prince of Songkla University.…”
Section: Methodsmentioning
confidence: 99%
“…Penetrating traumatic brain injury (PTBI) is much less common than blunt traumatic brain injury [1]. Larkin et al .…”
Section: Introductionmentioning
confidence: 99%